Question
upstudy study bank question image url

Express the given function \( h \) as a composition of two functions \( f \) and \( g \) so that \( h(x)=(f \circ g)(x) \), where one of the functions is \( 5 x-2 \). \( h(x)=(5 x-2)^{6} \) \( f(x)=\square \)

Ask by Ford Martinez. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( f(x) = x^6 \)

Solution

To express h(x) = (5x - 2)^6 as the composition (f ∘ g)(x) with one of the functions being 5x - 2, we can set   g(x) = 5x - 2 Then, since h(x) = (g(x))^6, we choose   f(x) = x^6 This gives us the composition:   (f ∘ g)(x) = f(g(x)) = (5x - 2)^6 = h(x). So the answer is:   f(x) = x^6.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To express the function \( h(x) = (5x - 2)^6 \) as a composition of two functions, we can identify \( g(x) \) as the inner function and \( f(x) \) as the outer function. Here, we can choose \( g(x) = 5x - 2 \) and then define \( f(x) = x^6 \). So, we have: \( g(x) = 5x - 2 \) \( f(x) = x^6 \) Therefore, the composition is \( h(x) = (f \circ g)(x) = f(g(x)) = f(5x - 2) = (5x - 2)^6 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy